EL REINO VISIGODO EN LA CONCEPCIÓN DE JULIÁN DE TOLEDO - García Herrero, Gregorio (Antigüedad y Cristianismo, 1995)
The analysis of the conceptual categories manifested in the works of Julian of Toledo in regards to the political realities, such as the kingdom and its habitans, shows that these are determined by the eschatological feelings of the autho and his view of History. While the regnum appears as a patrimonial reality bestowed on the monarch by means of the Real Unction ceremony, other terms, such as barbarus or gothus, are now mere anachronisms. The gens is used to differentiate the hispanogothic peoples from their neighbors. However, from our point of view, it is more relevant to pay attention to the response found in the works of Julian. This response defines the habitants of the Kingdom as populus christianus, which, in the general concept of History, substituted the populus iudaicus, with al1 the known important political consequences that brought about.